(untitled) (Physical Sciences and Technology, 2019)
Paper presents an analysis of the measurement procedure of the zenith and azimuth angles υ and φ in the X-ray emulsion chambers (XREC) of ADRON and PAMIR experiments. Earlier, asymmetry was observed in distributions of azimuth angles of gamma and hadron families. A detailed analysis of methodological errors in measuring θ, φ angles allowed us to establish the causes of the distortion of azimuth angles distributions. There are two reasons: systematic errors in the measurement of zenith angles by MBS-2 microscopes, used both in the PAMIR experiment, and in the ADRON experiment, and the inclination of XREC based on the subsidence. Calculations showed that the total systematic error Δυ≈4 ° completely explains the observed azimuthal asymmetry. Formulas for correcting θ and φ angles are given. The recalculation of the angles by the indicated formulas showed that this corrects the distribution of the azimuthal angles φ. The REC plane should be set relative to the horizontal with an accuracy of no worse than 1 degree in order to avoid distortion of the angular distributions.